Tinjauan Yuridis Pembayaran Transaksi Pihak Ketiga dengan Jaminan dari Perspektih Hukum Islam Kajian Atas Efektivitas Pelaksanaan Undang-Undang Perbankan Syariah pada Praktik Pembiayaan dengan Jaminan) - Ahmad Basraf; Efridani Lubis; Ade Salamah (Jurnal Hukum Jurisdictie, 2021)
Every financing always carries a risk. Therefore, the Bank asks for a Guarantee because it affects customer compliance to make payments of its obligations in accordance with the contract. In the principles of Islamic law, it is permissible to provide collateral/security held by the debtor, but not a necessity / obligation. Collateral must not be a determinant in providing financing or not made to ensure the return of capital, on the contrary, but to ensure that the recipient of the financing will carry out the conditions stipulated in the contract, including the return of the funds received.